2015
DOI: 10.1111/cas.12690
|View full text |Cite
|
Sign up to set email alerts
|

Non‐steady‐state hematopoiesis regulated by the C/EBPβ transcription factor

Abstract: Steady-state hematopoiesis responds to extracellular stimuli to meet changing demands and also to pathologically altered intracellular signaling. Granulocyte production increases following infection or in response to cytokine stimulation, and activation of the CCAAT/enhancer-binding protein β (C/EBPβ) transcription factor is required for such stress-induced granulopoiesis, whereas C/EBPα plays a critical role in maintaining steady-state granulopoiesis. Different roles of these C/EBP transcription factors in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
43
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 82 publications
(103 reference statements)
1
43
1
Order By: Relevance
“…65 to be increased in C/EBP--mediated emergency granulopoiesis in myeloid-derived suppressor cells (MDSCs). 66 In line with this, reports suggest iNOS is downstream to the C/EBP--mediated signaling in stress-induced granulopoiesis as shown in zebrafish. 67 The role of iNOS in stress-induced granulopoiesis could thus form a promising scope for future studies.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…65 to be increased in C/EBP--mediated emergency granulopoiesis in myeloid-derived suppressor cells (MDSCs). 66 In line with this, reports suggest iNOS is downstream to the C/EBP--mediated signaling in stress-induced granulopoiesis as shown in zebrafish. 67 The role of iNOS in stress-induced granulopoiesis could thus form a promising scope for future studies.…”
Section: Discussionmentioning
confidence: 61%
“…This correlates with our observation of decreased in vitro cytokine‐induced neutropoiesis in iNOS KO mice as compared to WT. Furthermore, iNOS may have a role in stress‐induced granulopoiesis, as iNOS expression was found to be increased in C/EBP‐β‐mediated emergency granulopoiesis in myeloid‐derived suppressor cells (MDSCs) . In line with this, reports suggest iNOS is downstream to the C/EBP‐β‐mediated signaling in stress‐induced granulopoiesis as shown in zebrafish .…”
Section: Discussionmentioning
confidence: 74%
“…37 The transcription factor of the leucine zipper basic region CCAAT/enhancer-binding protein b (C/EBPB) is a member of the C/EBP family. [51][52][53][54] Evidence has indicated that C/EBPB regulates cell differentiation, survival, proliferation, and metabolic processes by inhibition or activation of the target genes. A recent study showed that cells underwent accelerated apoptosis in Cebpbdeficient mice.…”
mentioning
confidence: 99%
“…26 The partial inhibition of CD11b expression by treatment with neutralizing anti-G-CSF antibody during DMSO-induced differentiation suggests that DMSO regulates the differentiation of HL-60 cells by several distinct pathways. 56,57 In summary, the present study showed that wild-type Kras regulates the differentiation of HL-60 cells via the Wnt/β-catenin signaling pathway. DMSO triggers Kras activation through the recruitment of Kras to the plasma membrane (1,2).…”
Section: Discussionmentioning
confidence: 51%
“…56 One dispensable activity may be C/EBPα activation of the C/EBPɛ gene, 56 with C/EBPα replaced by C/ EBPβ under stress conditions. 56,57 In summary, the present study showed that wild-type Kras regulates the differentiation of HL-60 cells via the Wnt/β-catenin signaling pathway. Accumulation of C/EBPα upregulates the expression of G-CSF receptor and stimulates mature granulopoiesis in HL-60 cells.…”
Section: Discussionmentioning
confidence: 51%